2017
DOI: 10.1007/s10709-017-9949-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of residual Triatoma infestans populations from Brazil by microsatellite

Abstract: In spite of long-term efforts to eliminate Triatoma infestans (Klug 1834) from Brazil, residual foci still persist in the states of Bahia and Rio Grande do Sul. Data on the genetic variability and structuring of these populations are however lacking. Using nine microsatellite loci, we characterized one residual T. infestans population from Bahia and four from Rio Grande do Sul, and compared them with bugs originally from an older focus in São Paulo; 224 bugs were genotyped. The number of alleles per locus rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…With respect to spraying, it has been reported that insect resistance to the chemical treatment employed (pyrethroid insecticides such as alpha-cypermethrin and deltamethrin) was not observed. In addition, Pessoa et al (2015) 14 and Belisário et al (2017) 15 demonstrated that the specimens of T. infestans strong genetic structure and little to no gene flow among populations, from the states of Bahia and RS, collected precisely in Santa Rosa and Doutor Maurício Cardoso. These municipalities, together with Santo Cristo, exhibited the last foci of T. infestans in this investigation and were susceptible to pyrethroid insecticide deltamethrin in laboratory tests, corroborating our field observations.…”
mentioning
confidence: 99%
“…With respect to spraying, it has been reported that insect resistance to the chemical treatment employed (pyrethroid insecticides such as alpha-cypermethrin and deltamethrin) was not observed. In addition, Pessoa et al (2015) 14 and Belisário et al (2017) 15 demonstrated that the specimens of T. infestans strong genetic structure and little to no gene flow among populations, from the states of Bahia and RS, collected precisely in Santa Rosa and Doutor Maurício Cardoso. These municipalities, together with Santo Cristo, exhibited the last foci of T. infestans in this investigation and were susceptible to pyrethroid insecticide deltamethrin in laboratory tests, corroborating our field observations.…”
mentioning
confidence: 99%
“…Despite the progress, the risk of vector transmission of Chagas disease persists due to the existence triatomine bugs with high colonization potential. The persistence of residual foci of Triatoma infestans in some municipalities in the states of Bahia and Rio Grande do Sul [90] could lead to the spreading of the disease.…”
Section: Chagas Diseasementioning
confidence: 99%